Potassium fertilization modulates potato (Solanum tuberosum L. V7) yield and rhizosphere microbiome dynamics - Yang, Jing; Han, Xiaodong; Li, Qi; Wang, Dong; Li, Yuankai; Zhang, Ziyi (Frontiers in Plant Science, 2025)
IntroductionPotassium (K) is a critical macronutrient essential for enzymatic activation, photosynthesis, metabolite transport, and stress resistance in plants. While K is known to influence soil microbial communities, the mechanistic relationships between K fertilization regimes, rhizosphere microbiome assembly, and crop productivity remain to be elucidated. This study investigated the effects of varying K fertilization rates on potato yield and associated rhizosphere microbial community dynamics throughout the key developmental stages.MethodsA field experiment using potato (Solanum tuberosum L. V7) was conducted in Inner Mongolia, China, during the 2024 growing season. Five K fertilization treatments (0, 120, 180, 240, and 300 kg/ha K2O) were implemented using a randomized complete block design with three replicates. Rhizosphere soil samples were collected at seedling, tuber initiation, and tuber bulking stages. High-throughput sequencing of bacterial 16S rRNA and fungal ITS1 regions was performed to characterize microbial communities. Taxonomic composition, α-diversity, β-diversity, and linear discriminant analysis effect size was conducted to assess the correlation of potato yield and microbial diversity.ResultsPotato yield exhibited a quadratic relationship with K application rate, reaching maximum productivity (66,786 kg/ha) at 240 kg/ha K2O. Bacterial communities, dominated by Proteobacteria, Acidobacteriota, Actinobacteria, and Gemmatimonadota, demonstrated notable resilience across treatments. Conversely, fungal communities displayed heightened sensitivity to K fertilization, with Shannon diversity indices negatively correlated with yield (r=-0.82, p<0.05). Moderate K application (180-240 kg/ha) significantly enhanced beneficial bacterial populations, particularly Pseudomonas species, while simultaneously suppressing pathogenic Fusarium and maintaining beneficial Mortierellomycota. Both bacterial and fungal communities exhibited distinct successional trajectories, with tuber expansion stage emerging as a critical transition point in community assembly.DiscussionThis investigation establishes 180-240 kg/ha K2O as the optimal application rate for maximizing potato yield while maintaining balanced rhizosphere microbial communities. K influences microbial community structure through multiple mechanisms, including ion-hormone interactions, nutrient activation processes, and pathogen regulation. These findings provide a theoretical framework for developing precision K fertilization strategies that enhance agricultural productivity while promoting the stability of the rhizosphere microbiome in potato cultivation systems.